Antiskin Inflammatory Activity of Black Ginger (Kaempferia parviflora) through Antioxidative Activity. (3rd April 2018) - Lee, Myung-hee; Han, Ah-Ram; Jang, Mi; Choi, Hyo-Kyoung; Lee, Sung-Young; Kim, Kyung-Tack; Lim, Tae-Gyu
Abstract : Kaempferia parviflora (Krachaidum (KD)) is a traditional herbal medicine and has properties that are beneficial for human health. In the current study, we sought to investigate the anti-inflammatory properties of KD extract (KPE). In mouse skin tissue, UV light representing solar wavelengths (sUV) increased COX-2 expression, while treatment with KPE reduced this effect. The anti-inflammatory activity of KPE was confirmed in in vitro models. MAPK signaling pathways were activated by sUV irradiation, and this was also repressed in the presence of KPE treatment. It is assumed that the anti-inflammatory activity of KPE is caused by the antioxidative effect. Furthermore, we confirmed the critical role of oxidative stress in sUV-induced COX-2 expression. We analyzed the polyphenol composition of KPE. Of the polyphenols identified, gallic acid, apigenin, and tangeretin were identified as the major polyphenols (at 9.31 ± 1.27, 2.37 ± 0.14, and 2.15 ± 0.19  μ g/mg dry weight, resp.). Collectively, these findings show that in the presence of sUV irradiation, KD has anti-inflammatory properties and antioxidative effects in the skin.